A Review on Significance of Ground Water Quality Assessment: Exploring the Complexities of Groundwater Quality and its Impact on Human Health and the Environment (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Many people throughout the world rely on groundwater water stored below the surface of theEarth for their daily water needs. The ecological stability of our world depends on it, and its quality hasan effect on human health. Natural processes, human activities, pollution dangers, and monitoringmethods are all relevant to this discussion. The continued availability of groundwater and the safety ofthe people who rely on it depend on our capacity to accurately assess and characterize its quality. In thisinvestigation, we will dig into the many facets of groundwater quality, illuminating the problems,potential solutions, and criticality of protecting this unseen resource.